2010
DOI: 10.1128/jb.01368-09
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliRNase R Has Dual Activities, Helicase and RNase

Abstract: In Escherichia coli, the cold shock response occurs when there is a temperature downshift from 37°C to 15°C, and this response is characterized by induction of several cold shock proteins, including the DEAD-box helicase CsdA, during the acclimation phase. CsdA is involved in a variety of cellular processes. Our previous studies showed that the helicase activity of CsdA is critical for its function in cold shock acclimation of cells and that the only proteins that were able to complement its function were anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
68
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 65 publications
5
68
2
Order By: Relevance
“…In the absence of CsdA, PNPase would be unable to function properly, thereby leading to the same impaired growth as is observed for a PNP Ϫ strain. The single chromosomal copy of rnr is unable to provide sufficient activity to overcome the absence of PNPase activity, but RNase R can complement when overexpressed (10). This scenario would explain the earlier complementation data.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the absence of CsdA, PNPase would be unable to function properly, thereby leading to the same impaired growth as is observed for a PNP Ϫ strain. The single chromosomal copy of rnr is unable to provide sufficient activity to overcome the absence of PNPase activity, but RNase R can complement when overexpressed (10). This scenario would explain the earlier complementation data.…”
Section: Discussionsupporting
confidence: 60%
“…In contrast to most exoribonucleases, RNase R is particularly adept at degrading highly structured RNA molecules (2,(5)(6)(7), and defining the mechanism by which it carries out this process is highly important (8,9). Escherichia coli RNase R contains an intrinsic RNA helicase activity (10), and recent work from our laboratory characterized this helicase and defined its relation to overall nuclease activity (8,9). In the E. coli protein, we also identified Walker A and Walker B motifs that are responsible for ATP binding and consequent RNA helicase activity, and found that they are conserved in most mesophilic bacterial genera, but are absent from thermophilic bacteria (8), suggesting that the helicase is important for RNase R function.…”
mentioning
confidence: 99%
“…In particular, RNase R has been observed to unwind and degrade completely dsRNA substrates of nearly 20 bp (4,7,21). Recent singlemolecule FRET data indicate that both RNase R and its homolog, the Rrp44 subunit of the eukaryotic exosome (22,23), advance 3′-to-5′ along dsRNA in steps of approximately four base pairs through internal elastic coupling of their binding and catalytic sites (24).…”
mentioning
confidence: 99%
“…Recent singlemolecule FRET data indicate that both RNase R and its homolog, the Rrp44 subunit of the eukaryotic exosome (22,23), advance 3′-to-5′ along dsRNA in steps of approximately four base pairs through internal elastic coupling of their binding and catalytic sites (24). RNase R mutants that lack the nuclease activity required for processive motion nonetheless may separate hybridized strands of RNA (21,25), presumably through an entirely different, distributive mechanism similar to that described for DEAD-box helicases under certain conditions (26). Although RNase R appears to have a minor preference for adenine (13), no significant sequence-dependent behavior has been reported for this enzyme.…”
mentioning
confidence: 99%
“…This helps the separation of the doublestranded RNA region immediately outside of the channel and leads the resulting single-stranded RNA to the channel for degradation (13). E. coli RNase R also possesses a RNA helicase activity in its CsdA domain that contributes to the degradation of double-stranded RNA (23). M. genitalium RNase R is able to degrade highly structured rRNA; however, it is sensitive to the aminoacyl-acceptor stem of tRNA and to RNA 2Ј-O-methylation (Ref.…”
Section: Discussionmentioning
confidence: 99%